2008
DOI: 10.1063/1.2937199
|View full text |Cite|
|
Sign up to set email alerts
|

The bone diagnostic instrument II: Indentation distance increase

Abstract: The bone diagnostic instrument ͑BDI͒ is being developed with the long-term goal of providing a way for researchers and clinicians to measure bone material properties of human bone in vivo. Such measurements could contribute to the overall assessment of bone fragility in the future. Here, we describe an improved BDI, the Osteoprobe II™. In the Osteoprobe II™, the probe assembly, which is designed to penetrate soft tissue, consists of a reference probe ͑a 22 gauge hypodermic needle͒ and a test probe ͑a small dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 39 publications
(37 reference statements)
1
72
1
Order By: Relevance
“…Previous studies using this device on bone have shown a high and significant correlation between reported indentation properties and modulus of toughness [15], fracture resistance [19], and crack growth toughness [13] determined using more traditional mechanical test approaches. These data provide some level of validation that indentation parameters from RPI correspond with mechanical variables from well-established mechanical testing methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using this device on bone have shown a high and significant correlation between reported indentation properties and modulus of toughness [15], fracture resistance [19], and crack growth toughness [13] determined using more traditional mechanical test approaches. These data provide some level of validation that indentation parameters from RPI correspond with mechanical variables from well-established mechanical testing methods.…”
Section: Discussionmentioning
confidence: 99%
“…1B). These three indentation parameters were selected from various reference point indentation (RPI) outcomes because they were the most common parameters used in previous studies [12,13,15,18,19].…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Recently, reference point indentation (RPI) was developed to enable assessment of bone mechanical properties in vivo. 1,2 This technique utilizes one of the two instruments to assess bone material-level properties: BioDent Hfc and OsteoProbe (ActiveLife Scientific, Santa Barbara, CA, USA). These instruments both indent the surface of bone in order to assess material properties, but they differ in a number of important details.…”
Section: Introductionmentioning
confidence: 99%
“…In a concerted effort to develop a reliable method to directly quantify fracture risk in living patients in a noninvasive manner, we have developed a new diagnostic instrument, the Reference Point Indentation Instrument [4] (RPI) (aka. Tissue Diagnostic Instrument [5], Bone Diagnostic Instrument [6][7][8], and Osteoprobe [9]) that uses a controlled indentation protocol to investigate the micro-mechanical response of the tibia to a defined loading regime. Clinical trials by Diez-Perez have shown the RPI to be successful at discriminating between patients with and without fragility fracture [4].…”
Section: Introductionmentioning
confidence: 99%